The Impact of Service Quality and Price Perception on Repurchase Intention at PT Nankai AGL - Meilyna, Jane; Pramesti, Elisabeth Dewi; Gunawan, Aang; Rachman, Ira (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
Freight forwarding service users' repurchase intentions are influenced by service quality factors and price perceptions in the international market. This study aims to investigate the influential factors in forming customers repurchase intentions at PT Nankai AGL, focusing on the relationship between service quality and price perceptions. Using a quantitative research design, this research collected survey data from 56 samples of PT Nankai AGL customers from 2022 to 2023. The tool used to assist the research is the Partial Least Square Structual Equation Modeling (PLS-SEM) method. This research hypothesizes that service quality and price perception have a significant effect on customer repurchase intentions. Based on the research results, it was found that the price perception variable (X2) had a significant effect on repurchase intention (Y) at PT Nankai AGL, while the service quality variable (X1) had no significant effect, either positively or negatively, on repurchase intention (Y).